Nora i Mexico - Exe Christoffersen, Erik (Peripeti, 2020)
In this article I try to apply a concept of materialistic and nomadic dramaturgy both to a perspective of Henrik Ibsen's text A Doll's House (1879), written in Italy, and to a review of a concrete creative process with the text as a framework for a dance performance, listed in Mexico 2019.